2018
DOI: 10.4317/medoral.22763
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to predict the onset of biphosphonate-related osteonecrosis of the jaw: A systematic review

Abstract: BackgroundThe goal of this paper was to identify available biomarkers to predict the onset of biphosphonate-related osteonecrosis of the jaw (BRONJ).Material and MethodsCase-control studies comparing the different concentrations of a series of molecules detected in serum and urine as matrices of BRONJ affected patients vs. non-affected were included. PRISMA guidelines for systematic reviews were used for the present paper. Two reviewers independently screened electronic databases (Medline, Web of science, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…2 Previous studies also suggest that serum C-terminal cross-linking telopeptide of type I collagen (CTX), serum receptor activator for nuclear factor k B ligand (RANKL) and osteoprotegerin (OPG) levels, and the RANKL/OPG ratio may be associated with the severity of MRONJ, but this remains controversial. 3,4,15,16 In the present study, we retrospectively analyzed the clinical data of MRONJ patients to identify the factors associated with severe disease (stage 3 MRONJ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies also suggest that serum C-terminal cross-linking telopeptide of type I collagen (CTX), serum receptor activator for nuclear factor k B ligand (RANKL) and osteoprotegerin (OPG) levels, and the RANKL/OPG ratio may be associated with the severity of MRONJ, but this remains controversial. 3,4,15,16 In the present study, we retrospectively analyzed the clinical data of MRONJ patients to identify the factors associated with severe disease (stage 3 MRONJ).…”
Section: Discussionmentioning
confidence: 99%
“…However, slow-response deGs exhibited enrichment in ossification and cartilage-associated signaling pathways. As reported by aghaloo et al (27) and lorenzo-Pouso et al (28), inflammation and inhibition of bone remodeling have been suggested as putative mechanisms of BronJ. While isolated evidence of resorption-generation imbalance (29), periodontal disease (7) and infection (30) has been discovered in patholog-ical research of BronJ, these hypotheses are treated as being exclusive and require validation (31).…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with the discussed literature, these molecular pathways have been explored in search of therapies or prevention strategies, such as the identification of biomarkers, and to a greater or lesser extent these have not helped with the discovery of conclusive strategies for these emerging matters. Once a landmark initiative, the use of serum CTX with a predictive or prognostic value for MRONJ is still highly debated . In this line, Fleisher et al reported on a cohort of 26 patients receiving BPs with CTX levels <150 pg/mL who underwent surgical management for BRONJ, or simply at‐risk patients who went through surgical interventions and who all exhibited a 100% positive response rate without relapse or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Once a landmark initiative, the use of serum CTX with a predictive or prognostic value for MRONJ is still highly debated. 6,43 the presence of variants that do not present exposed necrotic bone.…”
Section: Discussionmentioning
confidence: 99%